1981
DOI: 10.1111/j.1399-3054.1981.tb04496.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vitro treatment with ozone on the physical and chemical properties of membranes

Abstract: Treatment of microsomal membranes from cotyledons of Phaseolus vulgaris with ozone raises the liquid‐crystalline to gel lipid phase transition temperature and results in the formation of distinct domains of gel phase lipid in the membranes. Liposomes prepared from the total lipid extracts of ozone‐treated membranes undergo phase separations just a few degrees below the transition temperature for intact membranes, indicating that the formation of gel phase lipids is largely attributable to ozone‐induced alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Recent in vitro studies indicate that gel phase lipid forms when ' Supported by a grant-in-aid from the Natural Sciences and Engi- Waterloo, Ontario N2L 3G1 Canada lipid peroxidation is induced in isolated membranes (22,24). In fact, several lines of evidence indicate that free radical-induced lipid peroxidation plays a role in bringing about many of the deteriorative changes associated with plant senescence.…”
mentioning
confidence: 99%
“…Recent in vitro studies indicate that gel phase lipid forms when ' Supported by a grant-in-aid from the Natural Sciences and Engi- Waterloo, Ontario N2L 3G1 Canada lipid peroxidation is induced in isolated membranes (22,24). In fact, several lines of evidence indicate that free radical-induced lipid peroxidation plays a role in bringing about many of the deteriorative changes associated with plant senescence.…”
mentioning
confidence: 99%
“…PAN reacts with double bonds leading to the production of oxidation products (7). Indeed, Pauls and Thompson (19,20) have reported that chemical and physical changes in membrane lipids such as the breakdown of phospholipids, the loss of sterols from the membrane, and the formation of gel phase lipid membrane were induced by treating the isolated microsomal membrane from bean leaves with ozone in solution. However, the results obtained from isolated systems have not been confirmed in plant tissues.…”
mentioning
confidence: 99%
“…Membranes damaged by peroxidation of the polyunsaturated fatty acids by aging, ozone, or chemical oxidizing agents show marked increases in the temperature at which this change in molecular ordering occurs (4,20,21). Concomitant with this change in molecular ordering are marked decreases in the fluidity of the membrane (7,9), increases in the ratio of saturated to unsaturated fatty acids (9,21), and increases in the permeability of the membrane (11,19).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, data obtained by x-ray diffraction, fluorescence polarization, and studies on the temperature dependence of fatty acid spin labels indicate that cooperative changes in molecular ordering occur in liposomes, microsomes, and chloroplast and mitochondrial membranes at 10 to 20°C (20)(21)(22). Membranes damaged by peroxidation of the polyunsaturated fatty acids by aging, ozone, or chemical oxidizing agents show marked increases in the temperature at which this change in molecular ordering occurs (4,20,21). Concomitant with this change in molecular ordering are marked decreases in the fluidity of the membrane (7,9), increases in the ratio of saturated to unsaturated fatty acids (9,21), and increases in the permeability of the membrane (11,19).…”
Section: Discussionmentioning
confidence: 99%